Carbon Nanotube Interlayer Enhances Water Permeance and Antifouling Performance of Nanofiltration Membranes: Mechanisms and Experimental Evidence - Long, Li; Wu, Chenyue; Yang, Zhe; Tang, Chuyang Y (Environmental science & technology, 2022)
Interlayered thin-film nanocomposite (TFNi) membranes have been shown to achieve enhanced water permeance as a result of the gutter effect. Nevertheless, some studies report impaired separation performance after the inclusion of an interlayer. In this study, we resolve the competing mechanisms of water transport in the transverse direction vs that in the normal direction. To enable easy comparison, carbon nanotube (CNT)-incorporated TFNi membranes with an identical polyamide rejection layer but different interlayer thicknesses were investigated. While increasing the thickness of the CNT interlayer facilitates water transport in the transverse direction (therefore improving the gutter effect), it simultaneously increases its hydraulic resistance in the normal direction. An optimal water permeance of 13.0 ± 0.7 L m h bar , which was more than doubled over the control membrane of 6.1 ± 0.7 L m h bar , was realized at a moderate interlayer thickness, resulting from the trade-off between these two competing mechanisms. In this study, we demonstrate reduced membrane fouling and improved fouling reversibility for a TFNi membrane over its control without an interlayer, which can be attributed to its more uniform water flux distribution. The fundamental mechanisms revealed in this study lay a solid foundation for the future development of TFNi membranes toward enhanced separation properties and antifouling ability.